Effect of limestone calcium and magnesium ratio on micronutrients in alfalfa - Moreira, Adônis; Carvalho, Janice Guedes de; Moraes, Larissa Alexandra Cardoso; Salvador, João Odemir (Pesquisa Agropecuaria Brasileira, 2000)
This study evaluated the effect of limestone Ca:Mg ratios on micronutrients in alfalfa. A randomized block design was used with five relations of Ca:Mg ratios (1:0, 1:1, 2:1, 3:1 and 4:1) at a recommended limestone dosage of 3,900 kg ha-1. An additional treatment was included at a ratio of 3:1 with the dosage of 7,800 kg ha-1. All treatments had four replicates in a six-cutting number, in 35 days of interval. The variables analyzed were: concentration and quantity of B, Cu, Fe, Mn, and Zn in dry matter. The decrease of the concentration of B, Fe, Mn and Zn was obtained in the treatment that used twice the recommended dosage. The antagonic effect between Ca, applied as CaCO3, and Cu was not observed in the treatments. The concentration of micronutrients varied according to the cutting times.